Les violences envers les personnes trans* à l'université. Des conséquences sur la santé mentale aux pistes pour s’en sortir - Cha Prieur (Genre, Sexualité et Société)
Violence against trans* people in academia is a structural problem. Because of transphobia and cisnormativity, academia is not welcoming to trans* people. The article discusses the different strategies of trans* exclusion. There are only a few places for psychological support in and outside academia for trans* people dealing with this violence, as university-based and liberal psychotherapists are rarely trained in trans* realities. I propose some avenues for reflection to change the situation, such as training university staff and creating trans* networks. I finally present my clinical practice with trans* people involved in an academic environment.